A 500-year cycle of demographic expansion and contraction in the lower Yangtze and adjacent coastal region during the Holocene driven by East Asian summer monsoon oscillations - Deke Xu; Yuhai Wang; Keyang He; Hao Li; Yajie Dong; Jun Kuang; Zhigang Zhang; Bing Song; Yulong Niu; Guoping Sun; Yonglei Wang; Jiatong Lu; et al. (Quaternary Science Reviews, 2026)

Cadmium exposure and health outcomes:An umbrella review of meta-analyses - Wenzhuo Xu; Sainan Wang; Wenhua Ruan; Mingyue Hao; Kele Jiang; Hao Guo; Anyi Geng; Mengting Man; Zheng Hu; Yun Liu; Guifang Jin; Haiyan Shi; et al. (Environmental Research, 2025)

Longitudinal reconfiguration of multifaceted fish α and β diversity triggered by non-native species invasion in tropic rivers of Hainan Island - Dangen Gu; Chi Zhang; Gaojun Li; Meng Xu; Hui Wei; Miao Fang; Lu Shu; Xuejie Wang; Keyang Peng; Zhongguan Jiang; Fandong Yu (Journal of Environmental Management, 2025)

Numerical investigation of thermodynamic effect on cavitation performance and cavitation-vortex interaction in an inducer - Bin Xu; Xingyu Liu; Keyang Liu; Weibin Zhang; Yilin Deng; Xi Shen; Desheng Zhang; B.P.M (Bart) van Esch (Ocean Engineering, 2024)

Surface free radicals activated CoP/MoS2 sensors through electrocatalytic water splitting for enhanced NO2 sensing at room temperatures - Xixi Li; Xiao Wang; Zhaokun Sun; Feifei Li; Yao Fu; Keyang Zhao; Gang Zhao; Cunguang Zhu; Xijin Xu (Chemical Engineering Journal, 2024)

Synergetic effect of biochar and intermittent electricity stimulation on mitigating the adverse effects of tannic acid on anaerobic granular sludge in wastewater - Junxia Ni; Yihu Xu; Keyang Jiang; Ling Liu; Yunpeng Zhu; Xuelian Zou; Qian Gao; Jinhu Feng; Di Wu; Xiaopeng Yue; Wei Zhang; Shuangfei Wang; et al. (Journal of Water Process Engineering, 2024)

Multi-bioinspired alginate-based gel coatings formed by dynamic metal–ligand assembly for enhancing foliar affinity and rain-fastness of pesticides - Keyang Mai; Shujuan Yang; Xinyu Zhao; Riting Huang; Shuntian Huang; Congying Xu; Gaobo Yu; Yuhong Feng; Jiacheng Li (Chemical Engineering Journal, 2024)

Novel Selective Quantification of Zinpentraxin Alfa Biotherapeutic in the Presence of Endogenous Isomer in Plasma Samples of Idiopathic Pulmonary Fibrosis Patients Using Immunoaffinity LC–MS - Maoyin Li; Audrey Arjomandi; Xiaowei Sun; Erhu Lu; Tulika Tyagi; WeiYu Lin; Saloumeh K. Fischer; Surinder Kaur; Keyang Xu (The AAPS Journal, 2023)
Idiopathic pulmonary fibrosis (IPF) is a progressive fatal interstitial lung disease that affects three million patients worldwide and currently without an effective cure. Zinpentraxin alfa, a recombinant human pentraxin-2 (rhPTX-2) protein, has been evaluated as a potential drug candidate for the treatment of IPF. Clinical pharmacokinetic analysis of zinpentraxin alfa has been challenging historically due to interference from serum amyloid P component (SAP), an endogenous human pentraxin-2 protein. These molecules share an identical primary amino acid sequence and glycan composition; however, zinpentraxin alfa possesses α2,3-linked terminal sialic acid residues while SAP is an α2,6-linked isomer. By taking advantage of this only structural difference, we developed a novel assay strategy where α2,3-sialidase was used to selectively hydrolyze α2,3-linked sialic acid residues, resulting in desialylated zinpentraxin alfa versus unchanged sialylated SAP, following an immunoaffinity capture step. Subsequent tryptic digestion produced a unique surrogate asialo-glycopeptide from zinpentraxin alfa and allowed specific quantification of the biotherapeutic in human plasma. In addition, a common peptide shared by both molecules was selected as a surrogate to determine total hPTX-2 concentrations, i.e., sum of zinpentraxin alfa and SAP. The quantification methods for both zinpentraxin alfa and total hPTX-2 were validated and used in pharmacokinetic assessment in IPF patients. The preliminary results suggest that endogenous SAP levels remained largely constant in IPF patients throughout the treatment with zinpentraxin alfa. Our novel approach provides a general bioanalytical strategy to selectively quantify α2,3-sialylated glycoproteins in the presence of their corresponding α2,6-linked isomers. Graphical Abstract

Thermodynamic effect on attached cavitation and cavitation-turbulence interaction around a hydrofoil - Bin Xu; Keyang Liu; Jiali Deng; Xingyu Liu; Xi Shen; Desheng Zhang; Ailian Chang; Jiuyu Chen; Sijiang Chang (Ocean Engineering, 2023)

Review of the mechanism and control methods of anaerobic granular sludge calcification - Zhiwei Wang; Keyang Jiang; Yunpeng Zhu; Ling Liu; Xuelian Zou; Xiao Yang; Yihu Xu; Jian Zhang; Yubao Chen; Wenhua Gao; Shuangfei Wang (Journal of Water Process Engineering, 2023)

Blood lead levels of children exposed to e-waste: a systematic review and meta-analysis - Jintao Huang; Zhijun Zeng; Xijin Xu; Qianwen Tian; Keyang Zheng; Xia Huo (Environmental Science and Pollution Research, 2023)

Efficient selective adsorption of cytokine IL-6 and other middle-macromolecular toxins in the serum of uremia patients with specially designed porous hollow carbon spheres - Xiaohuan Zhao; Chong Wang; Boyang Xu; Jie Liang; Keyang Li; Yiqing Guo; Ming Gong; Yun Zhao; Yilun Huang; Yuehong Li; Ming Zhao; Daming Zhuang; et al. (Chemical Engineering Journal, 2023)

Experimental Study on Unsteady Cavitating Flow and Its Instability in Liquid Rocket Engine Inducer - Hao Wang; Jian Feng; Keyang Liu; Xi Shen; Bin Xu; Desheng Zhang; Weibin Zhang (Journal of Marine Science and Engineering, 2022)
To study instability in the unsteady cavitating flow in a liquid rocket engine inducer, visualization experiments of non-cavitating and cavitating flows inside a model inducer were carried out at different flow conditions. Visual experiments were carried out to capture the evolution of non-cavitating and cavitating flows in a three-bladed inducer by using a high-speed camera. The external characteristic performance, cavitation performance, and pressure pulsation were analyzed based on the observation of non-cavitation and cavitation development and their instabilities. Under non-cavitation conditions, the change of flow rate has a significant impact on the pressure pulsation characteristics in the inducer. The occurrence of cavitation aggravated the instability of the flow and caused the intensity of pressure pulsation at each measuring point to increase. This cavitation structure has strong instability, and the tail region is often accompanied by shedding cavitation clouds perpendicular to the blade surface.

Development and Translational Application of an Integrated, Mechanistic Model of Antibody-Drug Conjugate Pharmacokinetics - Siddharth Sukumaran; Crystal Zhang; Douglas D. Leipold; Ola M. Saad; Keyang Xu; Kapil Gadkar; Divya Samineni; Bei Wang; Marija Milojic-Blair; Montserrat Carrasco-Triguero; Bonnee Rubinfeld; Paul Fielder; et al. (The AAPS Journal, 2017)

Mechanism-Based Pharmacokinetic/Pharmacodynamic Model for THIOMAB™ Drug Conjugates - Siddharth Sukumaran; Kapil Gadkar; Crystal Zhang; Sunil Bhakta; Luna Liu; Keyang Xu; Helga Raab; Shang-Fan Yu; Elaine Mai; Aimee Fourie-O’Donohue; Katherine R. Kozak; Saroja Ramanujan; et al. (Pharmaceutical Research, 2015)

Recommendations for Validation of LC-MS/MS Bioanalytical Methods for Protein Biotherapeutics - Rand Jenkins; Jeffrey X. Duggan; Anne-Françoise Aubry; Jianing Zeng; Jean W. Lee; Laura Cojocaru; Dawn Dufield; Fabio Garofolo; Surinder Kaur; Gary A. Schultz; Keyang Xu; Ziping Yang; et al. (The AAPS Journal, 2015)

A Mechanistic Pharmacokinetic Model Elucidating the Disposition of Trastuzumab Emtansine (T-DM1), an Antibody–Drug Conjugate (ADC) for Treatment of Metastatic Breast Cancer - Brendan Bender; Douglas D. Leipold; Keyang Xu; Ben-Quan Shen; Jay Tibbitts; Lena E. Friberg (The AAPS Journal, 2014)